Analysis on Indoor Ventilation Environment of House Type Based on Architectural Aesthetics. (22nd February 2022) - Xu, Geng-Yang; Chen, Chang-Bing; Cai, Zheng-Qun
Abstract : Architectural aesthetics mainly creates architectural beauty according to the law of beauty and realizes the interaction between creative subject and object, and receptor. Its essence has been soaked and attached to all kinds of materialized carriers and behavioral subjects in the living environment. Through the aesthetic optimization of residential house type, this paper analyzes the ventilation efficiency of representative house type, which affects the prevention and control of community infectious diseases and the physical and mental health of residents. Take multiple measures to strengthen the aesthetic design of residential house type, and promote the healthy development of community ecology and the cultural inheritance of harmonious society. It is helpful for architectural designers to improve their understanding of the effect of natural ventilation and provide reference means for designers to reasonably organize indoor natural ventilation in architectural design.